Nilai Ibadat Dalam Perbuatan-perbuatan Harus (Al-Af’al Al-Mubahah): Tinjauan Terhadap Pemikiran Imam Ahmad Ibn Taymiyyah - Ramli, Rushdi (Jurnal Fiqh, 2010)
Islam pays a great deal of attention towards human deeds because every action human makes will have a profound effect on his or her life. In this regard, Islam has divided human deeds into five main categories which are wajib, sunnah, haram, makruh dan mubah. By observing what is obligatory and commendable acts of worship and avoiding what is haram and makruh a person will be able to become close to Allah S.W.T. and gain His pleasure. However Muslim scholars have different point of view regarding ?permissible deeds? as to what extend those actions can be regarded as ?part of worship? when they are being carried out with pious intention and in harmony with the Islamic law. This article discusses the position of mubah deeds through the view point of Ahmad Ibn Taymiyyah.